A comparative study of the level of cultural awareness about sports for educational cadres in the Karbala Governorate Center, according to gender and educational qualification - Marwah Ali Hamzah,; Hassan Ali Hussein,; Rahi Alasadi, Hasanain Jabbar (International Journal of Psychosocial Rehabilitation, 2026)
The researchers discussed the distinguished scientific and technological progress in all areas of life, and considering the field of physical education one of the most prominent areas of human knowledge that is developing and is still developing on the foundations and principles of its scientific research and the role of sport in our society. The study objectives to: 1. Knowing the level of cultural awareness about sport among the members of the research sample. 2. Knowing the difference in the level of cultural awareness about sport according to gender and specialization.Research hypotheses included: 1. There are significant differences between male and female teachers in the level of cultural awareness about sport. 2. There are significant differences in the level of cultural awareness about sport among educational cadres according to the educational qualification. As part of the study procedures, they used the descriptive method in the survey method and comparative studies to achieve the goals of the research. The research community also included male and female teachers in the Karbala Governorate Center. The research sample was chosen by (200) singles distributed to schools by (100) teachers and (100) schools. Through the results of the statistical analysis of the data and the study of the variables, the most important of which were reached. There are significant differences in the level of cultural awareness about sport among educational cadres according to the educational qualification, and there are significant differences between males and females in the level of cultural awareness about sport.